ParseKey+: A five-way strong authentication procedure as an approach to client/server impersonation avoidance using steganography for key encryption - Rahnama, Behnam; Elci, Atilla (My University, 2007)
This paper presents the ParseKey-, an approach to a new highly-secure and safe authentication service. The scheme includes authentication process for both client and server sides in addition to passwords of each side. ParseKey+ employs transposition to hide the encrypted key in a key file retrievable only by the other side knowing the indices and lengths of sub-keys inside ParseKey+ encrypted file. ParseKey+ avoids client and server impersonations in addition to mutual client/server authentication. There-fore, the ParseKey+ scheme avoids counter-reply attack. The key file is changed at each signing on procedure. The key file is an additional security beyond the login password which avoids client and server impersonation.
2007 International Conference on Security and Management, SAM'07 --
Keywords: Fake server; Five-way strong authentication; ParseKey+; Phishing; Steganography